Understanding and Mitigating Poverty Level of Maluku Province in the Context of Indonesian Unity: The Role of Pattimura University - Leunufna, Semuel (European Journal of Applied Sciences, 2025)
High poverty level of Maluku province relative to 38 provinces in Indonesia has been a concen and focus of discussions among Maluku community leaders for many years. The study provides elaborations on statistical findings regarding poverty of Maluku and discussed solutions to mitigate the poverty in Maluku and possibly leed in prosperity level in Indonesia. The author elaborated on three areas of development; higher education, joint collaborations in exploiting and developing agricultural biodiversity potentials, and exploitation of other natural resources especially gas and oil minings.